Eksplorasi Tumbuhan beracun di Cagar Alam Martelu Purba - Yunus Afifuddin; Lamek Marpaung; Yohanes Silitonga (Peronema Forestry Science Journal, 2015)
This research about of poisonous plant in the Explorationof Poisonous Plants on Martelu Purba Nature Preserve doing analysis identification, secondary metabolit, and potential development of the aspect local knowledge with survey local knowledge. The second is aspect biodiversity with analysis of vegetation data collection. And the third is aspect phytochemical with detect the contain of secondary metabolit. The exploration of poisonous plant in Cagar Alam Martelu Purba  finded 16 kinds of toxic plants. The result of this research shows that five kinds of toxic plants which has a greater chance that cultivated as asource of biopesticide is Latong andosari (Alstonia scholaris L.R. Br), Birah (Alocasia arifolia Hallier. F), Langge (Homalonema propinqua Ridl),  Hau palu-palu ni ogung (Canarium album Raeusch), Andor hutdali   (Dioscorea sp.), Flacourtia rukam Zoll. & Mortizi, Lang-lang habungan (Coleus scutellariodes (I). Benth), Latong anduri (Litsea sp.), Baringtonia sp, Silambau (Clidemia hirta Bl), Rube (Ficus lowii King), Rube-rube (Ficus sinuata Thunb), Sitorhom (Eugenia sp.), Tomu ring-ring (Saurauia pendula Blume), Dosih (Rubus moluccanus eelkek), and Tabar-tabar (Costus speciosus Sm.). Keywords : Poisonous plant, Martelu Purba Nature Preserved, Phytochemical, Biopesticide